Penerapan E-Customer Relationship Management pada Taman Kanak-Kanak Hanifa - Chairuna, Dina; Lisanti, Yuliana; Kuncoro, Engkos Achmad (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Maintaining relationships with customers is an important factor to be the key to success of Hanifa kindergarten as a pre-school institution. It requires a precise strategy to be executed and a system to support the strategy. The design method begins with several analyses on the running business processes and the external and internal factors that affect the school. The analyses are then followed by a SWOT Matrix and Internal-External Matrix which produce several alternative strategies to be implemented. The strategy formulation results in a website-based application of E-Customer Relationship Management (E-CRM) with features including three phases in Customer Relationship Management, which are acquire phase, enhance phase and retain phase. The analysis and system design is conducted using object-oriented analysis and design (OOA & D) as documented by notation Unified Modeling Language (UML).